City of endless night : a Pendergast novel - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Pendergast novel., 2018)
"FOR GOD'S SAKE, TELL US WHAT'S HAPPENED!" "VENGEANCE. VENGEANCE IS WHAT'S HAPPENED." It begins as a manhunt for Grace Ozmian, the missing daughter of a wealthy tech billionaire. At first, the NYPD assumes Grace, beautiful, reckless, and a regular feature of the local tabloids, has simply sped off on another wild adventure. But the case becomes something altogether different when the young woman's body is discovered in an abandoned warehouse in Queens, the head nowhere to be found. Lieutenant CDS Vincent D'Agosta quickly takes the lead. He knows his investigation will attract fierce scrutiny, so D'Agosta is delighted when FBI Special Agent A.X.L. Pendergast shows up at the crime scene also assigned to the case. "I feel rather like Brer Rabbit being thrown into the briar patch," Pendergast tells D'Agota, "because I have found you here, in charge. Just like when we first met, back at the Museum of Natural History." D'Agosta hopes the case will give Pendergast an opportunity to demonstrate his considerable abilities back in the city he has made home. But neither Pendergast nor D'Agosta are prepared for what lies ahead. It quickly becomes clear that a diabolical presence is haunting the greater metropolitan area, and Grace Ozmian was only the first of many victims to be murdered...and decapitated. Worse still, there's something unique to the city itself that has attracted its evil eye of the killer--or killers. As mass hysteria sets in, Pendergast and D'Agosta find themselves in the crosshairs of an opponent who has threatened the very lifeblood of the city. It'll take all of Pendergast's skill to unmask this most dangerous foe--let alone survive to tell the tale."--